Trends in deaths and disability-adjusted life-years of stroke attributable to high body-mass index worldwide, 1990–2019 - Guo, Xiucai; Li, Junxiao; Yin, Xueyan; Zhang, Ziping; Zhong, Qiongqiong; Zhu, Feng (Frontiers in Neurology, 2023)
The High body mass index (HBMI) is an independent risk factor for stroke. Previous studies in incremental burden to a rapid growth of stroke, especially attributable to the HBMI, are incomplete and lag behind. We aim to assess global burden of stroke attributable to the HBMI based on a public database online.Materials and methods: Study data was taken from the Global Burden of Disease, Injuries, and Risk Factors Study; deaths, the Disability-Adjusted Life-Years (DALYs), and their age-standardized rates were screened. The join point regression was used, wherein age-standardized rates were referred to temporal trends in disease burden.Results: Deaths of stroke attributable to the HBMI worldwide were on the rise during 1990-2019, with an increase of 88.75%. Age-standardized the DALYs were on the rise during 1990-2003 but decline during 2003-2013, with a turning point in 2013 and an increasing trend since then (the Annual Percentage Change (APC) = 0.30%, P < 0.05). China, India, Indonesia, the Russian Federation, and the United States of America shared in sequence the leading deaths and the DALYs in 2019. The Socio-Demographic Index (SDI) was associated with an increasing trend in age-standardized deaths (R = −0.24, P < 0.001) and age-standardized the DALYs (R = −0.22, P = 0.0018), respectively.A range of indicators for global burden of stroke attributable to the HBMI were on the rise for the past three decades. Tremendous efforts worldwide should be in place to control and treat for stroke attributable to the HBMI, especially in regions with high-middle and middle SDIs, and among middle-aged and aged populations.